An Investigation of Conflict Resolution Strategies for the Students of Elementary School Teacher Education Study in Online Learning during the COVID-19 Pandemic - Rahayu, Galih Dani Septiyan; Maftuh, Bunyamin; Malihah, Elly (Mimbar Sekolah Dasar, 2021)
This study aims at identifying various types of conflicts experienced by students of elementary school teacher study program during online learning of elementary social studies learning courses during the COVID-19 pandemic, and determining the strategies they used to resolve conflicts they encountered . This study uses a descriptive research method with a survey design. The research participants were 4th semester students of the PGSD study program in a private university in the West Java region, totaling 243 that consisted of 182 female students and 61 male students. The instruments used in this study were interviews that were used to identify the conflicts experienced by students during online learning, and closed questionnaires that were distributed to determine the strategies used to resolve the conflicts; which were  analyzed descriptively. Based on the data obtained from the interviews, it was revealed that the conflicts experienced by students during online learning were completing group assignments, bullying between students, discriminatory attitude, and acknowledging/taking goods/works of others without asking permission. Meanwhile, based on the data obtained from the questionnaires regarding the students' strategies in resolving conflicts, it was found that students used cooperative strategies in resolving these conflicts.